Corrosion and tribocorrosion study of 316L steel, Ti–6Al–4V and Ti–10Zr–10Nb–5Ta. (3rd April 2019) - Carquigny, S.; Takadoum, J.; Ivanescu, S.
ABSTRACT: In this paper, corrosion and tribocorrosion tests have been conducted on three biomaterials: Ti–6Al–4V and 316L steel that are well-known commercial biomaterials and Ti–10Zr–10Nb–5Ta, a new biomaterial elaborated in a levitation-melting furnace. Tests have been conducted in five different electrolytes: NaCl (9g/l), Ringer's solution, phosphate buffered saline solution (PBS) with and without an addition of bovine serum albumin (BSA). Two amounts of BSA were used: 1 and 5 g/l. In NaCl solution, Ringer's solution and PBS solution, Ti–10Zr–10Nb–5Ta presents the best corrosion resistance. Conversely, in the presence of proteins, 316L steel shows better resistance to corrosion in comparison with Ti–10Zr–10Nb–5Ta and Ti–6Al–4V. During tribocorrosion tests, the surfaces have been submitted to friction against an alumina ball at open circuit potential (OCP). Measurement of wear rate at the end of the tests indicates clearly that 316L steel shows better resistance to material removal in comparison with Ti–10Zr–10Nb–5Ta and Ti–6Al–4V.